Odpowiedź :
Odpowiedź:
6x - 3 = 45
6x = 45 + 3
6x = 48 | :6
x = 8
3x + 21 = 18
3x = 18 - 21
3x = -3 | : 3
x = -1
5x - 6 = 4x + 1
5x - 4x = 1 + 6
x = 7
3(x - 5) = x + 1
3x - 15 = x + 1
3x - x = 15 + 1
2x = 16 | : 2
x = 8
9x - 2 (x + 1) = 7x + 2
9x - 2x - 2 = 7x + 2
9x - 2x - 7x = 2 + 2
0 = 4
6x + 35 = 5 (x + 7) + x
6x + 35 = 5x + 35 + x
6x - 5x - x = 35 - 35
0 = 0
Szczegółowe wyjaśnienie:
Odpowiedź:
1.
6x-3=45
6x=48 /:6
x=8
2.
3x+21=18
3x=-3 /:3
x=-1
3.
5x-6=4x+1
x=7
4.
3(x-5)=x+1
3x-15=x+1
2x=16 /:2
x=8
5.
9x-2(x+1)=7x+2
9x-2x-2=7x+2
0=4
brak rozwiązania, równanie sprzeczne
6.
6x+35=5(x+7)+x
6x+35=5x+35+x
0=0
równanie tożsamościowe, każda liczba spełnia to równanie